Development of Islet Cryopreservation for Type 1 Diabetes Cell Therapy - Han Hengxin; Zhan Taijie; Cui Mengdong; Yang Jiamin; Chen Liang; Xu Yi (Zhileng xuebao)
In recent years, cell therapy technology for type 1 diabetes has advanced rapidly, but the lack of donor pancreatic islets and the time and space mismatch between donor and recipient limits its clinical application. Cryopreservation technology provides a way to solve this problem. However, the survival rate and functionality of pancreatic islets that are preserved by traditional cryopreservation methods are poor, and it is difficult to achieve the required standard of clinical application. This study classifies and summarizes the principles of islet cryopreservation and the factors that cause islet damage during cryopreservation. It summarizes the development of pancreatic islet cryopreservation technology in recent years in terms of the inhibition of ice crystal damage, protective agents, and hypoxia injury. Due to the development of interdisciplinary research in materials science, molecular biology, and cryobiology, many new materials and methods have been developed in the field of islet preservation, which has further improved the quality of pancreatic islets after cryopreservation. However, there are few high-throughput vitrification methods developed for islet preservation. In addition, more research is needed on the potential adverse effects and protective mechanisms of new technology and materials for islet cryopreservation. In follow-up research, the development of new materials and technologies, especially high-throughput preservation technology, and the mechanism of low-temperature damage in the field of pancreatic islet cryopreservation will be investigated.